2017
DOI: 10.1002/ejsp.2255
|View full text |Cite
|
Sign up to set email alerts
|

The rhetorical complexity of competitive and common victimhood in conversational discourse

Abstract: Much current research on collective victimhood acknowledges the role of rhetoric but does not fully address the implications for micro‐level variation in personal expressions of victimhood. The focus has tended to be on individual differences in collective victimhood construals where people may either see their group as the sole possessor of victim status or may incorporate other groups into an inclusive category. Although recent research sees a strategic element in some ‘inclusivity’, we argue that all claims… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 55 publications
(64 reference statements)
2
35
0
Order By: Relevance
“…A second limitation concerns with McNeill, Pehrson, and Stevenson's () recent criticism of existing research on competitive victimhood for focusing on interindividual variability in expressions of victimhood while overlooking intraindividual variability. McNeill et al .…”
Section: Discussionmentioning
confidence: 99%
“…A second limitation concerns with McNeill, Pehrson, and Stevenson's () recent criticism of existing research on competitive victimhood for focusing on interindividual variability in expressions of victimhood while overlooking intraindividual variability. McNeill et al .…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that participants' answers shifted in the process of the discussions. Although it was beyond the scope of this article to analyze the conversational and discursive processes of these discussions (e.g., McNeill et al, 2017), we reported which themes were more common than others. However, given that not every group member was asked to speak to each point that was raised, it is impossible to provide exact frequencies of endorsement.…”
Section: Strengths and Limitationsmentioning
confidence: 96%
“…We focused on the semantic, explicit level of the content (Boyatzis, 1998;Braun & Clarke, 2006). We did not analyze the group dynamics, or the rhetoric and discourse of these conversations (e.g., McNeill, Pehrson, & Stevenson, 2017), because this was beyond the scope of our research questions. Instead, our goal was to map out themes in peoples' discussion of the individual and intragroup processes resulting from their ingroup's collective victimization.…”
Section: Analytic Proceduresmentioning
confidence: 99%
“…On the other hand, the victim status may threaten the group’s sense of power and agency and be stigmatizing in that it implies weakness and vulnerability (Ferguson, Burgess, & Hollywood, ; Shnabel & Nadler, ; Vollhardt & Nair, ). Therefore, the adoption of the victim status is also flexible and rhetorical, and it can be used or rejected in different contexts and for different reasons (Ferguson et al, ; McNeill, Pehrson, & Stevenson, ). In the following, we further discuss expressions of victimhood from the perspective of victim and perpetrator groups.…”
Section: Construals Of Collective Violence Among Victim and Perpetratmentioning
confidence: 99%